Pengaruh EPS, PBV dan ROE terhadap Harga Saham pada Perusahaan Sektor Teknologi di BEI pada Periode 2022-2024 - Syahputri Anggraini; Dian Ayu Andriani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the effect of Earnings Per Share (EPS), Price to Book Value (PBV), and Return on Equity (ROE) on stock prices in technology sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research was motivated by inconsistencies between financial performance indicators and stock price movements in several technology companies. This study applied a quantitative approach using secondary data obtained from annual financial reports. The sample consisted of 10 technology companies selected through purposive sampling, resulting in 30 observations. Data were analyzed using multiple linear regression supported by SPSS software. Prior to hypothesis testing, classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The findings indicate that EPS, PBV, and ROE simultaneously have a significant effect on stock prices. Partially, EPS has a negative and significant effect, PBV has no significant effect, while ROE has a positive and significant effect on stock prices. The coefficient of determination shows that the independent variables explain 29% of stock price variation, while the remaining 71% is influenced by other factors outside the research model.